Mineral Liberation Studies Of Complex Gold Ore From Peranggih Prospect, Pahang - Muhammad, Amirul Asraf (Universiti Sains Malaysia, 2018)
The Peranggih prospect which is located to the North East of current Selinsing Gold Mine where the mineralization of gold took place within similar regional shearing structure that hosting Selinsing and Buffalo Reef deposits were studied. The focus of this research work is concentrate on identification composition of mineral content and percentage of mineral liberation at different size fraction of the sample from Peranggih sites. The mineral composition is analysed by using XRF. Mineral phase determination and quantification is analysed by using XRD. The morphological study from each size fraction is determined by using optical microscope and SEM. Before XRF analysis is carried out, LOI analysis is conducted as to remove volatile phases in the sample where the value of LOI is quite low which is 3.6%. The result from XRF obtain indicate the value of Si is high which is 31.6% followed by Al and Fe both of them are 10.1% and 4.2% respectively. Then mineral phase analysis has been done which content of silica minerals is the highest among the othermetallic mineral such as Arsenopyrite (FeAsS), Galena (PbS), and Hematite (Fe2O3) while the value for Quartz and others is about 84.0%. In morphological studies, the observation of sample and other physical properties under Tabletop SEM indicate the morphology of the mineral usually in form of irregular in shape and flaky. For mineral liberation studies, the degree of mineral liberation attain at size fraction of (-0.075) mm is 22.37% of mineral liberation. The percentage of mineral liberation increase as decreasing of the size fraction.